EFEK AMFETAMIN TERHADAP ULTRASTRUKTUR SEL SPERMATOGENETIK TIKUS - Alfiah Hayati (The East Java Biological Society, 2001)
The research was conducted to evaluate the effect of amphetamine as pshycostimulan drug on ultrastructure spermatogenic cells of male rats (Rattus norvegicus L.). Ultrastructure spermatogenic cells described from six male rats of Wistar strain. They were divided in to 2 groups (control and treatment group). Four mg/kg/days amphetamine were given sub-cutaninjection. In control to injection with physiologic saline. The last of the treatment the rat were killed after 100 days the amphetamine injection. The testis were released into fixative solution. Ultrastructure morphologic analysis of the testis were evaluate of quantitative to assess the effect of amphetamine on spermatogenic cells. Observation of spermatogenic cells (Spermatogonia, Spermatocyte, and Spermatyd cells) were done under the electrone microscope. The result of this experiment showed different morphologically from the amphetamine- treated group and their respective control. In the treatment groups, Spermatogonia, Spermtocyte, and spermayd cells less endoplasmic reticulum than normal spermatogenic cells (control). More vacuolization in membrane line of Spermatogoium cells and in cytoplasm of Spermatocyte, and Spermatic cells than normal spermatogenic cells (control).